The Composition and the Structure of MCC/Eisosomes in Neurospora crassa - Yang, Qin; Kempken, Frank (Frontiers in Microbiology, 2020)
MCC/eisosomes are protein-organized domains in the plasma membrane of fungi and algae. However, the composition and function(s) of MCC/eisosomes in the filamentous fungus Neurospora crassa were previously unknown. To identify proteins that localize to MCC/eisosomes in N. crassa, we isolated proteins that co-purified with the core MCC/eisosome protein LSP-1, which was tagged with GFP. Proteins that co-fractionated with LSP-1:GFP were then identified by mass spectrometry. Eighteen proteins were GFP-tagged and used to identify six proteins that highly colocalized with the MCC/eisosome marker LSP-1:RFP, while five other proteins showed partial overlap with MCC/eisosomes. Seven of these proteins showed amino acid sequence homology with proteins known to localize to MCC/eisosomes in the yeast Saccharomyces cerevisiae. However, homologs of three proteins known to localize to MCC/eisosomes in S. cerevisiae (Can1, Pkh1/2, and Fhn1) were not found to colocalize with MCC/eisosome proteins in N. crassa by fluorescence microscopy. Interestingly, one new eisosome protein (glutamine-fructose-6-phosphate aminotransferase, gene ID: NCU07366) was detected in our studies. These findings demonstrate that there are interspecies differences of the protein composition of MCC/eisosomes. To gain further insight, molecular modeling and bioinformatics analysis of the identified proteins were used to propose the organization of MCC/eisosomes in N. crassa. A model will be discussed for how the broad range of functions predicted for the proteins localized to MCC/eisosomes, including cell wall synthesis, response and signaling, transmembrane transport, and actin organization, suggests that MCC/eisosomes act as organizing centers in the plasma membrane.